Photoinduced cholesteric helix inversion in some systems containing chiral α,β-unsaturated ketones - Krivoshey, A.I.; Shkolnikova, N.I.; Chepeleva, L.V.; Kutulya, L.A.; Pivnenko, N.S. (Functional Materials, 2004)
Cholesteric helix inversion induced with UV irradiation has been revealed in the liquid crystal (LC) system based on nematic 4-pentyl-4 '-cyanobiphenyl (5CB) which contains left-handed helix inducing chiral dopant of 3( R)-methyl-6-arylidenecyclohexanone series. A further irradiation results in increasing right-handed helical twisting in the system till photostationary state is reached. The twisting extent in this state exceeds three times that in the initial mixture and remains unchanged under further UV light action. The effect under consideration must be caused by reversible photochemical E,Z-isomerization of the chiral dopant molecules. This was proven by preparative photochemical synthesis of the corresponding Z-isomer and independent study of its properties as a chiral dopant in 5CB. It is shown that a principal difference exists between photoinduced changes in the LC systems containing chiral a,P-unsaturated ketones, 3(R)-methylcyclohexanone and (+)-isomenthone derivatives. Обнаружена фотоиндуцированная УФ облучением инверсия знака холестерической спирали в жидкокристаллической системе на основе нематического 4-пентил-4'-цианоби-фенила (5ЦБ), содержащей хиральную добавку серии левозакручивающих 3(5)-метил-6-арилиденциклогексанонов. Продолжение облучения после точки инверсии усиливает правое закручивание в системе до достижения фотостационарного состояния. В этом состоянии степень холестерического закручивания превышает в три раза таковое для исходной смеси и не изменяется при дальнейшем продолжительном действии света. Обнаруженный эффект обусловлен обратимой фотохимической E-Z изомеризацией, что доказано препаративным фотохимическим синтезом соответствующего Z-изомера и независимым изучением его поведения как хиральной добавки в 5ЦБ. Показано принципиальное отличие фотоиндуцированных изменений в системах, содержащих хиральные «^-ненасыщенные кетоны, производные 3(5)-метилциклогексанона и (+)-изоментона. Виявлено фотоіндуковану УФ опроміненням інвєрсію знаку холестеричної спірилі у рідкокристалічній системі на основі нематичного 4-пентил-4'-ціанобіфенілу (5ЦБ), яка містить хіральну домішку серії лівозакручуючих 3(5)-метил-6-ариліденциклогекса-нонів. Продовження опромінення після точки інверсії посилює праве закручування у системі до досягнення фотостаціонарного стану. У цьому стані ступінь холестеричного закручування перевищує втричі відповідний показник для вихідної суміші і не змінюється при подальшому тривалому впливі світла. Виявлений ефект обумовлений оборотною фотохімічною E-Z ізомеризацією, що доведено препаративним фотохімічним синтезом відповідного Z-ізомеру та незалежним дослідженням його поведінки як хіральної домішки в 5ЦБ. Показано принципову відмінність фотоіндукованих змін у системах, які містять хіральні а,в-ненасичені кетони, похідні 3(5)-метилциклогексано-ну та (+)-ізоментону.